2014
DOI: 10.3109/02770903.2014.903968
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in work-related asthma: surveillance data from California, Massachusetts, Michigan, and New Jersey, 1993–2008

Abstract: Objective To characterize work-related asthma by gender. Methods We analyzed state-based sentinel surveillance data on confirmed work-related asthma cases collected from California, Massachusetts, Michigan, and New Jersey during 1993–2008. We used Chi-square and Fisher’s Exact Test statistics to compare select characteristics between females and males. Results Of the 8239 confirmed work-related asthma cases, 60% were female. When compared to males with work-related asthma, females with work-related asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…This finding is slightly higher than previously reported results from California, Massachusetts, Michigan, and New Jersey work-related surveillance systems where 68.6% of individuals with work-related asthma in the agriculture, forestry, and fishing industry were males. 37 Other studies from work-related asthma surveillance systems reported that more of the work-related asthma patients are females. 38,39 However, in these reports no separate results for men and women by industry and occupation were presented.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is slightly higher than previously reported results from California, Massachusetts, Michigan, and New Jersey work-related surveillance systems where 68.6% of individuals with work-related asthma in the agriculture, forestry, and fishing industry were males. 37 Other studies from work-related asthma surveillance systems reported that more of the work-related asthma patients are females. 38,39 However, in these reports no separate results for men and women by industry and occupation were presented.…”
Section: Discussionmentioning
confidence: 99%
“…The different workplace exposures between men and women should be taken into consideration when considering gender effects on asthma. Women with work-related asthma are more likely to work in healthcare, educational services, retail trade, and education [109]. While all asthmatics overall are more likely to own a furry pet compared to nonasthmatics (49.9 % versus 44.8 %), and to frequently allow them into the bedroom (68.7 %), asthmatic women have a higher chance of owning a pet compared to asthmatic men [110].…”
Section: Differences In Perception and Behaviormentioning
confidence: 99%
“…Late‐onset asthma has been described as a distinct asthma phenotype, associated with higher morbidity . Similarly, occupational asthma can develop at any time during the working life, and older age at diagnosis has been associated with worse outcomes . Nonetheless, few studies have investigated the impact of occupational exposures on respiratory health at later career stages.…”
Section: Introductionmentioning
confidence: 99%